Roles of partitioning‐defective protein 6 (Par6) and its complexes in the proliferation, migration and invasion of cancer cells. (September 2017) - Ruan, Lingling; Shen, Yanting; Lu, Ziwen; Shang, Dongsheng; Zhao, Zhicong; Lu, Yongjin; Wu, Yanfang; Zhang, Yafei; Tu, Zhigang; Liu, Hanqing
Summary: A pivotal regulator of cell polarity and homeostasis, partitioning‐defective protein 6 (Par6) forms multicomponent complexes that not only regulate cell polarity and stabilize cell morphology, but have also been demonstrated to participate in the proliferation, migration and invasion of cancer cells. The transforming growth factor (TGF)‐β and extracellular signal‐regulated kinase (Erk) 1/2 pathways are the most thoroughly studied pathways involving Par6 in many cancers. Aurothiomalate has been used to disrupt the interaction between Par6 and atypical protein kinase C within the multicomponent complexes, and has been shown to effectively block transformed growth and metastasis in vitro and/or in vivo in a variety of cancers, including pancreatic, prostate and lung cancers, as well as alveolar rhabdomyosarcoma. It is likely that with further revelations regarding the critical roles of Par6 in cancer initiation, progression and metastasis, targeted therapies against Par6 will be discovered and prove effective preclinically, and hopefully clinically, in cancer treatment.